Factors Affecting Auditor Performance and Competence : A Systematic Literature Review - Matakupan, Suryana Salomi; Zaimar, Fina Ruzika; Nisrina, Ulfah Laila; Lukman, Siti Diva Syarifah; Hidayatullah, Andi Muh Syukur (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
A Systematic Literature Review (SLR) was conducted to explore the relationship between auditor performance, competency, and audit quality. Of the 86 articles reviewed, the PRISMA flowchart was used to select those relevant and related to the research objectives. Twenty-seven articles discussed auditor performance, auditor capability, and audit quality. Despite extensive research on each of these aspects, gaps remain in understanding how they interact and impact overall audit practice. Factors impacting auditor performance are divided into three categories: internal factors, organizational factors, and environmental factors. Education and training, experience and exposure, and professional development are various factors that impact auditor capability. This performance and competency directly and indirectly impact audit quality. These findings are expected to offer valuable insights for audit practitioners, regulators, and academics, contributing to the improvement of audit practice and strengthening public trust in the audit profession. The importance of a holistic approach to auditor professional development, taking into account workload, competency development, and various other factors, is a key focus. Furthermore, time management and personal emotions also significantly impact auditor performance and capabilities, ultimately affecting audit quality. Keywords:Auditor; Auditor Performance; Auditor Competence; Audit Quality; Systematic Literature Review